How to take feedback seriously - CHAN, David (Institutional Knowledge at Singapore Management University, 2019)
Publicresponses to incidents are a valuable source of feedback. While negativefeedback may cause discomfort, it is important for policymakers to learn toprocess and respond better to such views.